ROLE OF SERUM ZINC AND COPPER AND ZINC/ COPPER RATIO IN ALOPECIA AREATA - Elldin Al- Jaff, Ashwaq Najjem (Iraqi Journal of Pharmaceutical Sciences, 2017)
Alopecia areata is considered as a major health problem, its importance is attributed to itsrecent increased incidence in our population. Till now, there is no exact cause for alopecia areataalthough researchers thought it’s an autoimmune disease.This clinical study was designed to evaluate the role of trace elements (zinc and copper) in patientswith alopecia areata. Twenty patients were diagnosed as having alopecia areata with an age range(10-40 years) were involved in this study. Normal subjects of the same age group were alsoevaluated as control. The level of serum Zn and Cu were measured by flame atomic absorptionspectrophotometry in both control and patient group. And the ratio of Zn/Cu was also estimated.The results of patients group revealed that serum Zn level was significantly lower than those ofcontrol (p<0.001), while serum Cu was significantly higher than that of control group (p=0.002).Furthermore, Zn/Cu ratio of patients group was significantly lower than that of control subjects(p<0.001). These results suggest the possible role of Zn and Cu level in alopecia areata. In additionto that the utility of measuring Zn/ Cu ratios for the diagnosis of the disease over that ofdetermining the serum level of Zn or Cu alone since this ratio clearly reflects the severity of theprogress.